Pengaruh Motivasi, Kompensasi Finansial dan Komunikasi terhadap Kinerja Karyawan Supermarket Pamella Sembilan - Arifiyanto Arifiyanto; Jajuk Herawati; Epsilandri Septyarini (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study intends to find the impact of motivation on employee performance, the effect of financial compensation on employee performance, the effect of communication on employee performance, the effect of motivation, financial compensation, and communication on employee performance at the Pamella Sembilan Wonosari Supermarket. This study used quantitative methods with a total population of 150 people and a total sample of 110 people. Data will be collected through the primary data method from distributing questionnaires which are then tested for normality, heteroscedasticity, and multicollinearity. The method used is regression analysis. This research results if motivation has a positive and significant effect on employee performance with a coefficient of 0.202, sig. 0.002 <0.005 and t-count 3.242 > t-table 1.98. There is a positive and significant impact of financial compensation on employee performance, the acquisition of a coefficient of 0.222, a sig value of 0.001 <0.005 and t-count 3.329 > t-table 1.98. There is a positive and significant effect of communication on Employee Activity with a coefficient of 0.391. sig. value 0.001 < 0.005 and t-count 3.570 > t-table 1.98, as well as motivational factors, financial compensation and communication have a positive and significant impact on employee performance simultaneously, the acquisition of F count is 33.070 > F-table 2.96 and sig 0.000 <0.05. Keywords: Motivation, Financial Compensation, Communication, Employee Performance